1994
DOI: 10.5254/1.3538675
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation, Properties and Potential Applications of “Diimide-Hydrogenated” Styrene-Butadiene (HSBR) and Polybutadiene (HBR) Thermoplastic Elastomers

Abstract: Our unique diimide-based process for preparing HNBR latex from NDR latex without the use of hydrogen, noble metal catalysts or solvents has now been successfully extended to the preparation of hydrogenated thermoplastic elastomers latexes directly from SBR or BR latex precusors. Commercially available SBR latex such as SBR 1502 can be readily reduced to high saturation levels (95+%) via the diimide reduction technique. Latex cast films of the highly reduced elastomer show excellent ozone and oxidation resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…This happens in the low-temperature region only. 9 Contrary to the expectation, the thermal stability of HSBR is less than that of SBR in the presence of air in the temperature range between 280 and 480°C and the thermal stability of SBR in air is higher than in nitrogen. 21 A similar observation was made here also.…”
Section: Tga Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…This happens in the low-temperature region only. 9 Contrary to the expectation, the thermal stability of HSBR is less than that of SBR in the presence of air in the temperature range between 280 and 480°C and the thermal stability of SBR in air is higher than in nitrogen. 21 A similar observation was made here also.…”
Section: Tga Resultscontrasting
confidence: 39%
“…7,8 It has also been claimed that newer thermoplastic elastomeric latexes could be obtained by this technique. 9 Scientifically, it is interesting to alter the properties of the butadiene units of SBR and to generate new polymers with controlled crystalline segments. Both the microstructure of butadiene units and the styrene level are expected to influence the hydrogenation reaction, although a literature search revealed that these have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Wideman 4 discovered that an elastomer in latex form can be converted directly into its saturated analogue when treated with hydrazine able solvent, or hydrogen gas. Parker et al 5 later 30% hydrogen peroxide was added dropwise over the specific period of time with the help of a dropprepared hydrogenated styrene-butadiene rubber (SBR) latex by the diimide reduction technique ping funnel. The volume of H 2 O 2 was varied from 10 to 40 mL (0.09 to 0.35 mol).…”
Section: Introductionmentioning
confidence: 99%
“…Since this early effort, a number of studies have been published in this area, but all of them mainly focus on enhancing the properties of latexes based on acrylonitrile-butadiene [6][7][8][9][10][11] and styrene-butadiene rubbers. [12][13][14][15] Until now, no group has taken advantage of the hydrogenation reaction to generate polyethylene (PE) latex. Such a route is potentially of great interest to produce a purely linear PE-based latex with very different properties from those of branched PEs produced by free radical emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%